Patient Risk Factors Associated with 30- and 90- Day Readmission after Ventriculoperitoneal Shunt Placement for Idiopathic Normal Pressure Hydrocephalus in Elderly Patients: A Nationwide Readmission Study. (16th November 2020) - Koo, Andrew B; Elsamadicy, Aladine A; Lin, I-Hsin; David, Wyatt; Reeves, Benjamin; Santarosa, Corrado; Cord, Branden; Malhotra, Ajayy; Kahle, Kristopher T; Matouk, Charles C
Abstract: INTRODUCTION: Unplanned hospital readmissions have increasingly been used as a quality metric for valued care. For idiopathic normal pressure hydrocephalus (iNPH), risk stratifying patients and identifying those who are likely to fare well after ventriculoperitoneal shunt (VP) surgery may help improve quality of care and reduce unplanned readmissions. METHODS: The Nationwide Readmission Database years 2013 - 2015 was queried. Elderly patients (≥65 years old) undergoing VP shunt surgery were identified using the ICD-10-CM coding system. Unique patient linkage numbers were used to follow patients and identify 30- and 31 to 90-day readmission rates. Patients were grouped by no readmission (Non-R), readmission within 30 days (30-R), and readmission within 31 to 90 days (90-R). Weighted multivariate analysis assessed factors associated with 30- and 90-day readmissions. RESULTS: We identified 7, 199 elderly patients undergoing VP shunt surgery for iNPH. 1, 413 (19.6%) patients were readmitted (30-R: n = 812 [11.3%] vs. 90-R: n = 601 [8.3%] vs. Non-R: n = 5, 786). The most common inpatient complications observed were extracranial postoperative infection (30-R: 7.0%, 90-R: 5.6%, Non-R: 4.3%), genitourinary complication (30-R: 4.6%, 90-R: 2.7%, Non-R: 2.1%), and intracranial hemorrhage (30-R: 2.8%, 90-R: 1.6%, Non-R: 0.6%). The most prevalent 30- and 90-day complications seen among the readmitted cohort were mechanical complication of nervous system device implant (30-R: 16.1%, 90-R: 12.4%), extracranial postoperative infection (30-R: 10.4%, 90-R: 7.0%), and subdural hemorrhage (30-R: 6.0%, 90-R: 16.4%). On multivariate regression analysis, age, diabetes, and renal failure were independently associated with 30-day readmission; female sex and 26–50 th household income percentile were independently associated with reduced likelihood of 90-day readmission. Having any complication during the index admission was independently associated with both 30- and 90-day readmission. CONCLUSION: Our study suggests that mechanical device complications, postoperative infection and subdural hemorrhage are the most common drivers for patient 30- and 90-day readmission for elderly patients with iNPH undergoing VP shunt surgery, and that having any complication during the index hospitalization is the greatest independent predictor for unplanned hospital readmission.